ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI TERJADINYA KECURANGAN AKUNTANSI (FRAUD) DI PEMERINTAH KOTA JAYAPURA (Studi Kasus Pada Pemerintah Kota Jayapura Di Kota Jayapura) - Irvan Krisna Arsad; Agustinus Salle; Mariolin Sanggenafa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to analyze factors affecting the occurrence of fraud (fraud) trend in the Government of Jayapura City. This research was conducted on 18 Government agencies in Jayapura City. Datacollection in this research was used questionnaire to the civil servant (PNS) working on Organization of Regional Region (OPD) Government of Provinsi Papua. The sampling technique was used in this research is purposive sampling. The number of samples taken as much as 150 respondents. Data analysis techniques using Partial Least Square (PLS) or Smart PLS 3.0 Based on the results of the analysis using the PLS test tool shows that the effectiveness of internal control does not affect thefraud of accounting (Fraud) in Jayapura City Government, organizational culture has no effect on fraud accounting (Fraud) in Jayapura City Government, the compensation suit does not affect theaccounting fraud in the Government of Jayapura City, (Fraud) in Jayapura, procedural justice has no effect on accounting fraud in the Government ofJayapura City, organizational commitment hasan effect on accounting fraud (Fraud) in Jayapura City Governmental System, distributive justice has no effect on accounting fraud (Fraud) in the Government of Jayapura City